Nonprotein Structures from Mycobacteria: Emerging Actors for Tuberculosis Control. (6th May 2012) - Lopez-Marin, Luz M.
Abstract : Immune response to Mycobacterium tuberculosis, the causal agent of tuberculosis, is critical for protection. For many decades, consistent to classical biochemistry, most studies regarding immunity to the tubercle bacilli focused mainly on protein structures. But the atypical, highly impermeable and waxy coat of mycobacteria captured the interest of structural biologists very early, allowing the description of amazing molecules, such as previously unknown carbohydrates or fatty acids of astonishing lengths. From their discovery, cell wall components were identified as important structural pillars, but also as molecular motifs able to alter the human immune response. Recently, as new developments have emerged, classical conceptions of mycobacterial immune modulators have been giving place to unexpected discoveries that, at the turn of the last century, completely changed our perception of immunity vis-à-vis fat compounds. In this paper, current knowledge about chemical and ultrastructural features of mycobacterial cell-wall is overviewed, with an emphasis on the relationships between cell-wall nonpeptide molecules and immune response. Remarks regarding the potential of these molecules for the development of new tools against tuberculosis are finally discussed.